Measurement of the isolated prompt photons production cross section in pp collisions at √s=7TeV - Khachatryan, V. (2011)
The differential cross section for the inclusive production of isolated prompt photons has been measured as a function of the photon transverse energy ETγ in pp collisions at √s=7TeV using data recorded by the CMS detector at the LHC. The data sample corresponds to an integrated luminosity of 2.9pb-1. Photons are required to have a pseudorapidity |ηγ|<1.45 and ETγ>21GeV, covering the kinematic region 0.006<xT<0.086. The measured cross section is found to be in agreement with next-to-leading-order perturbative QCD calculations. © 2011 American Physical Society.